2014
DOI: 10.1108/ijotb-17-04-2014-b005
|View full text |Cite
|
Sign up to set email alerts
|

Employee job satisfaction and organizational performance: The role of conflict management

Abstract: Organizational conflict is often thought of as a malady to be avoided or quickly resolved. Such views neglect the potential value of conflict—that is, the constructive management of conflict—to organizational outcomes. Managerial practices resulting in too little conflict may shape and reflect an organization hypersensitive to discord, dissent, and innovation. But management practices promoting excessive conflict may overload an organization with information, rendering it incapable of reaching timely decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 65 publications
3
31
1
1
Order By: Relevance
“…Employee satisfaction is not only a result of positive assessments of employee work experience, but also an effect of HR practices such as performance appraisal processes, wage structures, training and career development, and work-life balance (Shmailan, 2016;Aldakhil, Wu, Rezaei, & Cobanoglu, 2017). Furthermore, Chi and Gursoy (2009) and Coggburn and Bradbury (2014) examine the connection between employee satisfaction and customer satisfaction directly on the company's financial performance. Their study found that there was no significant direct effect on employee satisfaction with company financial performance.…”
Section: Employee Satisfaction (E1)mentioning
confidence: 99%
“…Employee satisfaction is not only a result of positive assessments of employee work experience, but also an effect of HR practices such as performance appraisal processes, wage structures, training and career development, and work-life balance (Shmailan, 2016;Aldakhil, Wu, Rezaei, & Cobanoglu, 2017). Furthermore, Chi and Gursoy (2009) and Coggburn and Bradbury (2014) examine the connection between employee satisfaction and customer satisfaction directly on the company's financial performance. Their study found that there was no significant direct effect on employee satisfaction with company financial performance.…”
Section: Employee Satisfaction (E1)mentioning
confidence: 99%
“…We follow the view that conflict has productive as well as destructive potential (Assael, 1969;Jehn, 1997;de Dreu and van de Vliert, 1997;Pelled, Eisenhardt, andXin, 1999, Rahim, 2002;Coggburn, J., Battaglio, R. and Bradbury, M., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, while five of the nine studies came from China, there was only one that was completed in the United States (Coggburn et al, 2014). It is recommended that more studies be performed in the U.S and across different cultural groups in the U.S. More cross-cultural studies, which investigate the relationship between conflict management styles, job satisfaction, and job performance is needed.…”
Section: Recommendations For Future Directionsmentioning
confidence: 99%
“…The existence of a conflict between employees is associated with lower levels of job satisfaction (Bisseling & Sobral, 2011). Coggburn et al (2014) found that employees who had been involved in a serious conflict in the workplace had lower job satisfaction and performed lower than those who had not been involved in a serious conflict. found that when employees had lower levels of job satisfaction, they also had lower levels of job performance.…”
Section: Conflict Management Styles Relationship With Job Satisfactiomentioning
confidence: 99%
See 1 more Smart Citation